Epidemiology of ciprofloxacin resistance and its relationship to extended-spectrum beta-lactamase production in Klebsiella pneumoniae isolates causing bacteremia - DURMUŞOĞLU, LÜTFİYE (OXFORD UNIV PRESS INC, 2000)
A prospective study of Klebsiella pneumoniae bacteremia was performed in 12 hospitals in 7 countries, Of 452 episodes of bacteremia, 25 (5.5%) were caused by ii, pneumoniae that was resistant in vitro to ciprofloxacin. Extended-spectrum beta-lactamase (ESBL) production was detected in 15 (60%) of 25 ciprofloxacin-resistant isolates, compared with 68 (16%) of 427 ciprofloxacin-susceptible strains (P = .0001), Multivariate analysis revealed that risk factors for ciprofloxacin resistance in ii. pneumoniae included prior receipt of a quinolone (P = .0065) and an ESBL-producing strain (P = .012), In all, 18% of ESBL-producing isolates were also ciprofloxacin-resistant. Pulsed-held gel electrophoresis showed that 11 of the 15 ciprofloxacin-resistant ESBL-producing strains belonged to just 4 genotypes, suggesting that patient-to-patient transmission of such strains occurred. The close relationship between ESBL production and ciprofloxacin resistance is particularly worrisome because the first reported instance of plasmid-mediated ciprofloxacin resistance has been in an isolate of K. pneumoniae also possessing an ESBL.
Keywords: ESCHERICHIA-COLI; QUINOLONE RESISTANCE; INFECTIONS; EMERGENCE